Art and emotion: the variety of aesthetic emotions and their internal dynamics - Przybysz, Piotr (Interdisciplinary Studies in Musicology, 2020)
The aim of this paper is to propose an interpretation of aesthetic emotions in which they are treated as various affective reactions to a work of art. I present arguments that there are three different types of such aesthetic emotional responses to art, i.e., embodied emotions, epistemic emotions and contextual-associative emotions. I then argue that aesthetic emotions understood in this way are dynamic wholes that need to be explained by capturing and describing their internal temporal dynamics as well as by analyzing the relationships with the other components of aesthetic experience.